PENGARUH PENERAPAN PEMBELAJARAN TGT DILENGKAPI MEDIA POWER POINT SISWA PADA MATERI STRUKTUR ATOM DAN SPU - Fitri Hartati; Fitri Refelita (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research aimed at knowing whether the use of TGT (Teams Games Tournament) cooperative learning model completed with Power Point media resulted better student learning achievement than the use of TGT cooperative learning model on Atomic Structure and Periodic System of the Elements lesson at the tenth grade of State Islamic Senior High School 4 Kampar in the Academic Year of 2017/2018. This research was Quasi-experiment with pretest and posttest design conducted in two classes—the first experimental group taught by using TGT cooperative learning model completed with Power Point media and the second experimental group taught by using TGT cooperative learning model. Simple random sampling technique was used in this research. The techniques of collecting the data were interview, preliminary data test that was homogeneity test, final data tests that were pretest and posttest, and documentation that was used to strengthen the obtained data. The research findings showed that posttest mean score of the first experimental group was 79 and the second group was 76,25. Final data analysis was using t-test, so it was obtained that tobserved was 2.21 and ttable was 2.02 at 5% significant level. tobserved was higher than ttable, so H0 was rejected and Ha was accepted. It meant that there was an effect of implementing TGT cooperative learning model completed with Power Point media toward student learning achievement on Atomic Structure and Periodic System of the Elements lesson at State Islamic Senior High School 4 Kampar, and the coefficient of effect was 11.38%.